Smart Recycle Dustbin with WIFI Monitoring System - Khairulisham, Nurul Mushahrafah Binti Khairulisham; Hassan, Hasliza (Progress in Engineering Application and Technology, 2023)
Smart recycle bin with a WIFI monitoring system has taken place to improve waste management. Therefore, objective of this project is to make recycling easier. It also makes it easier for people to put their trash in the bin. This project produces because of three problem statement which is the location of the dustbin is usually filthly and smelly, animal constantly open the lid of trash cans to find food and difficult for garbage collectors to collect unseparated rubbish. This project would include four types of sensors to detect four types of garbage: plastic, metal, paper, and wet garbage. This is due to the fact that in this project, the system would sperate the garbage when the items are contained within the garbage. The wastes are tracked by smart bins using a wifi system integrating the telegram based information system.. As a result, the employee connected to a wireless network from the dustbin to monitor the level of garbage in the bin. Finally, this project would make the environment cleaner and healthier for humans.